Film censorship regulators in Malaysia and Bangladesh - Islam, Md. Zahidul (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Regulatory bodies and its primary activity are to protect public interest. It is established on the basis of legal instruction. Regulatory bodies practice a supervisory function such as imposing requirements, restrictions and conditions in relation to any activity and safeguarding compliance or enforcement. The aim of this paper is to examine the film censorship regulators in Malaysia and Bangladesh. The researcher mainly adopted qualitative methods. The information has taken from many readings, articles, books, newspapers and statutes. The researcher also conducted interview with the member of the film censorship board, directors and actors of both countries. For this, the researcher used semi-structured form of interview. Film censorship law playing an important role to protect public from negative influence and it is working as a mechanism to protect society.